Exploring Resilience, Coping and Wellbeing in Women of Refugee Background Resettled in Regional Australia - Hawkes, Clare; Norris, Kimberley; Joyce, Janine; Paton, Douglas (Frontiers in Psychology, 2021)
This study aimed to address a significant gap in the literature by investigating how WoRB conceptualise resilience and identify factors that WoRB endorse as contributing to their wellbeing and coping during resettlement. Qualitative interviews were conducted with a group of 21 individuals (nine WoRB and 12 service providers). Thematic analysis identified that WoRB struggled to define resilience, with endorsed factors not fitting with current hegemonic Western understandings and theoretical understandings of resilience. The findings also highlighted how religious practice, finding a community, and having a sense of meaning and contribution in their daily life were significant coping and wellbeing factors during resettlement, however, were difficult to access in regional resettlement locations. Results of the current study are discussed regarding theoretical and practical implications, taking into consideration the unique vulnerabilities experienced by WoRB resettled in regional locations of Australia